Storm Castle Supplementary Reading Material - Roderick Hunt (Oxford Reading Tree, 1993)
This title offers teaching support material - guided reading cards, and teacher's notes included free with each pack of Oxford Reading Tree books. It contains Take-Home cards for every storybook from Stages 1 - 9 and has a website with downloadable photocopy masters.